(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Making the tertiary management of eye diseases improved and widely available for all social groups in all parts of Ukraine is a pressing challenge for not only the Ministry of Health, but also for the state. Purpose: To provide scientific and theoretical assessment of establishing a new branch of ophthalmology, cyber-ophthalmology. Results: We demonstrated that the studied issue is relevant and important in the light of developments in tele- and cyber-medicine, expansion of application of information technologies to and introduction of artificial intelligence in medicine and in particular in ophthalmology. Conclusion: Cyber-ophthalmology is becoming reality and a systematically important branch of ophthalmology. Research in and developments of this branch are essential for providing tertiary eye disease management and improved disease treatment efficacy for all social groups.